ChemInform Abstract: Niphateolide A: Isolation from the Marine Sponge Niphates olemda and Determination of Its Absolute Configuration by an ECD Analysis. Issue 52 (10th December 2015) - Tsukamoto, Sachiko; et al.,
Abstract: Title compound is isolated as an inseparable stereoisomeric mixture at C‐17.